PENERAPAN TEKNIK KONTRAK KONTINGENSI DALAM KONSELING KELOMPOK UNTUK MENINGKATKAN DISIPLIN MAHASISWA - Mulyawan, I Nyoman Rajeg (LPPM IKIP PGRI Bali, 2019)
This research is a classroom action research applied in counseling guidance services. The purpose of the study is to describe the discipline of students after being given group counseling services. 24 research subjects were students of the Counseling Guidance Study Program of IKIP PGRI Bali in the odd semester of 2018/2019. Student discipline data were collected by observation techniques, questionnaires and discipline scales. Actions in the form of counseling services with contingency contract techniques accompanied by rewards and punishments are given to students who have less disciplined attitudes and behaviors. The study design followed the PTK pattern that began with planning, implementing actions, observing / collecting data / analyzing data and reflecting. The results of the research through the stages of cycle I and cycle II can be described that the implementation of the counseling process of student discipline attitudes increased in cycle I increased by 20% and cycle II there was an increase of 30%. The average percentage of scores of students' discipline attitudes after the second counseling is 90%. This means that there is still a 10% tendency for disciplinary violations committed by students. In this regard disciplinary enforcement in the campus environment should be carried out in a compact and there are synergies from various components of the academic community. Disciplinary behavior of students in the first cycle has changed 10% and in the second cycle increased by 23% or an average of 83% of the discipline behavior of students. If described the average attainment of students' attitudes and disciplinary behavior after being given group counseling services reaches 91%. It can be suggested that the character of student discipline can be formed through the growth of awareness from within through what is heard, seen, because it is important to be considered by all academicians to be able to grow the character of discipline in the campus.